Global tracking of agrifood research and innovation for meeting food security and sustainable development goals - Compton, Julia; Stads, Gert-Jan; Barrett, Christopher B.; Herrero, Mario; Arndt, Channing; Prasad, P. V.; Zurek, Monika; Khetarpal, Ravi (T20 Indonesia, 2022)
Achieving global food security, alongside other Sustainable Development Goals, will not be possible without massive increases in investment in agrifood research and innovation. Innovation is needed in policy, social institutions, finance, and technology. Crucial areas of agrifood innovation are under-funded, including reducing food waste and producing nutritious food sustainably. Transparent tracking of research and innovation can highlight gaps in coverage, incentivize public and private investors to prioritize innovation that delivers global goals, and overcome constraints to uptake. We propose that the G20 provide pooled funding to a global multi-stakeholder agrifood research and innovation tracker, which will report results regularly to G20 Ministers and other policy makers.